Electoral Violence and the Ethnic Question in Nigeria: Analysis of the 2023 Elections - Chineyemba, Lydia Isioma; Chukwudi, Celestina Ekene; Ezebuilo, Paul Chibuike (JPPUMA: Jurnal Ilmu Pemerintahan dan Sosial Politik UMA (Journal of Governance and Political UMA), 2024)
Violence has become a serious threat, birthing crime, insecurity, and ethnic hatred that threaten national unity. While violence has remained an obstacle to the peaceful conduct of elections, it assumed a disturbing dimension in Lagos during the 2023 elections, where ethnicity was weaponized to polarise the nation. Whereas studies on electoral violence abound in literature, the desperation and impunity that trailed the 2023 elections and the tribal hatred it generated are dimensions of electoral violence requiring investigation. Therefore, this paper aims to highlight the violence that characterized the 2023 elections in Lagos State. It examined the ethnic bigotry that triggered the violence and its implications for peaceful coexistence and national unity. A qualitative data collection method uses secondary data from books, journals, newspapers, and magazines. Content analysis is chosen for better analysis of the study. Employing race and ethnicity and relative deprivation theories, the study found that ethnic violence was a scheme deviously politicized to instigate electoral violence in the bid to retain political power. Findings from the study showed that the violence threatened peaceful coexistence and the sense of brotherhood among Nigerians. It recommended stringent sanctions for the perpetrators of violence and the parties they represent. Policymakers will benefit from this study as it will provide the information needed for policymaking on handling electoral and non-electoral violence.